A synthetic analysis of greenhouse gas emissions from manure amended agricultural soils in China - Fengling Ren (Nature Portfolio, 2017)
Abstract Application of manure has been recommended as an effective strategy to to mitigate climate change. However, the magnitude of greenhouse gases emission derived by application of manure to agricultural soils across environmental conditions still remains unclear. Here, we synthesized data from 379 observations in China and quantified the responses of soil nitrous oxide (N2O), carbon dioxide (CO2) and methane (CH4) emissions to manure (Org-M) in comparison to chemical fertilizers (Min-F) or non-fertilizers (Non-F). The results showed that N2O, CO2 and CH4 emissions were significantly affected by Org-M compared to Min-F (percentage change: −3, +15 and +60%, P < 0.05) and Non-F (percentage change: +289, +84 and +83%, P < 0.05), respectively. However, at the same amount of total N input, Org-M decreased soil N2O emission by 13% and CH4 emission by 12%, and increased soil CO2 emission by 26% relative to Min-F in upland soils. For paddy soils, N2O, CO2 and CH4 emissions differed by −3%, −36% and +84% between Org-M and Min-F (i.e., Org-M minus Min-F). Thus, practices such as application of manure instead of chemical fertilizer and decreasing nitrogen input rate need to be highly considered and optimized under different soils and climate conditions to mitigate GHGs emission in China.